2019
DOI: 10.1016/j.jaccas.2019.09.022
|View full text |Cite
|
Sign up to set email alerts
|

A Thrombus in Transit Complicating Acute Pulmonary Embolism

Abstract: A 51-year-old man presented with acute pulmonary embolism. He was found to have a large intracardiac thrombus in transit across a patent foramen ovale. He underwent anticoagulation and urgent surgical thrombectomy with good outcome. ( Level of Difficulty: Beginner. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…When a patient presents with an atrial thrombus, while in SR, the etiology of this finding must be further investigated. While the presence of the RA thrombi in the setting of submassive PE (defined as hemodynamic stability with right heart strain), is an occasional finding (although more common in massive PE defined as hemodynamic instability plus right heart strain), it is the concomitant LA thrombus that has created this clinical dilemma [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When a patient presents with an atrial thrombus, while in SR, the etiology of this finding must be further investigated. While the presence of the RA thrombi in the setting of submassive PE (defined as hemodynamic stability with right heart strain), is an occasional finding (although more common in massive PE defined as hemodynamic instability plus right heart strain), it is the concomitant LA thrombus that has created this clinical dilemma [1].…”
Section: Discussionmentioning
confidence: 99%
“…A shunt between the venous and arterial system, or RA to LA, known as paradoxical emobli, is a possibility for the patient's findings. The most common transatrial shunt is a PFO, which is found in about 25% of patients [1]. Other less common causes of shunts are extracardiac arteriovenous connections, like a patent ductus arteriosus or pulmonary arteriovenous fistula [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations